2010
DOI: 10.1016/j.beth.2008.12.004
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Clinical Trial of Cognitive-Behavioral Therapy and Applied Relaxation for Adults With Generalized Anxiety Disorder

Abstract: This randomized clinical trial compared cognitive-behavioral therapy (CBT), applied relaxation (AR), and wait-list control (WL) in a sample of 65 adults with a primary diagnosis of generalized anxiety disorder (GAD). The CBT condition was based on the intolerance of uncertainty model of GAD, whereas the AR condition was based on general theories of anxiety. Both manualized treatments were administered over 12 weekly 1-hour sessions. Standardized clinician ratings and self-report questionnaires were used to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
107
1
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(124 citation statements)
references
References 39 publications
9
107
1
7
Order By: Relevance
“…There is considerable evidence that intolerance of uncertainty (IU) is a cognitive vulnerability factor for worry (Koerner & Dugas, 2008;Ladouceur, Gosselin, & Dugas, 2000; Mediators of repetitive negative thinking 4 Sexton, Norton, Walker, & Norton, 2003;van der Heiden, Melchior, Muris, Bouwmeester, Bos, & van der Molen, 2010) and an important maintaining factor for GAD (Behar, DiMarco, Hekler, Mohlman, & Staples, 2009;Dugas, Gagnon, Ladouceur, & Freeston, 1998). Intervention trials have found that changes in IU are associated with improvements in worry and anxiety symptoms during cognitive behavioral therapy (CBT, Dugas et al, 2003;Dugas et al, 2010). …”
Section: Introductionmentioning
confidence: 99%
“…There is considerable evidence that intolerance of uncertainty (IU) is a cognitive vulnerability factor for worry (Koerner & Dugas, 2008;Ladouceur, Gosselin, & Dugas, 2000; Mediators of repetitive negative thinking 4 Sexton, Norton, Walker, & Norton, 2003;van der Heiden, Melchior, Muris, Bouwmeester, Bos, & van der Molen, 2010) and an important maintaining factor for GAD (Behar, DiMarco, Hekler, Mohlman, & Staples, 2009;Dugas, Gagnon, Ladouceur, & Freeston, 1998). Intervention trials have found that changes in IU are associated with improvements in worry and anxiety symptoms during cognitive behavioral therapy (CBT, Dugas et al, 2003;Dugas et al, 2010). …”
Section: Introductionmentioning
confidence: 99%
“…The treatment has been tested in four published randomised clinical trials, with results showing that it is more efficacious than a waiting list control, 34,35 supportive therapy 36 and applied relaxation. 37 The findings also show that 60-77% of patients attain GAD remission and that 50-55% achieve high-end state functioning following the treatment. The CBT protocol developed by Dugas and Robichaud (i.e.…”
Section: Cognitive Behavioural Therapymentioning
confidence: 60%
“…Plus spécifiquement, nous voulions évaluer si ce traitement psychologique est efficace dans la réduction des symptômes de dépression et d'anxiété associés à une maladie cardiaque (par exemple, perte d'intérêt pour les activités quoti diennes, difficultés de sommeil, inquiétudes envahissantes, comporte ments d'évitement). Contrairement aux protocoles de traitement des études menées précé -demment, le protocole utilisé ici tient compte de la situation particulière des patients cardiaques et il est issu de manuels de traitements empiriquement validés (Barlow, 2002 ;Dugas, 2002 ;Leahy et Holland, 2000).…”
Section: La Présente éTudeunclassified
“…Le traitement offert aux patients est issu d'un compte rendu de nos expériences cliniques avec des patients ayant une maladie cardiaque, combiné aux éléments des protocoles de traitement de la dépres -sion majeure et des troubles anxieux empiriquement validés auprès des populations en bonne santé physique (Barlow, 2001 ;Dugas, 2002 ;Leahy et Holland, 2000). Contrairement aux protocoles de traitement habituels, celui-ci met l'accent sur l'impact émotionnel de la maladie cardiaque et des contraintes imposées par celle-ci (par exemple, perte d'emploi, de mobilité, etc.…”
Section: Protocole De Traitementunclassified